2018
DOI: 10.1111/tid.12964
|View full text |Cite
|
Sign up to set email alerts
|

Impact of donor and recipient cytomegalovirus serology on long‐term survival of lung transplant recipients

Abstract: Our review of the impact of CMV managed differently across eras suggests in lung transplantation there is no independent influence of D/R CMV serostatus on 10-year survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Previous studies have suggested that donor and recipient cytomegalovirus mismatch increases the risk of mortality in LTx patients. 28,29 Similar results were reported in our model in which cytomegalovirus mismatch was found to be a significant risk factor. Similar pattern was also seen when considering ECMO use.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have suggested that donor and recipient cytomegalovirus mismatch increases the risk of mortality in LTx patients. 28,29 Similar results were reported in our model in which cytomegalovirus mismatch was found to be a significant risk factor. Similar pattern was also seen when considering ECMO use.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies reported that donor and/or recipient CMV serology alone was associated with a higher risk of mortality among HSCT [ 38 , 39 ] and SOT patients [ 31 , 40 , 41 ]. On the other hand, Mabilangan et al [ 42 , 43 ] found no association between donor/recipient CMV serology and 10 years mortality among heart or lung transplant recipients. One potential explanation for the similar survival rates of CMV and non-CMV patients in our study may be the limited follow-up time of 1 year, which is comparatively shorter than other analyses of survival which reported outcomes based on extended follow-up periods of 5 years or longer [ 34 36 , 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Native lung disease was chosen as it demonstrates consistent associations with post-lung transplant outcomes. 11 In addition, pre-transplant CMV serostatus matching has been associated with lung transplant patient survival variable 12 and, therefore, included as an additional variable. For illustration purposes, we provide Kaplan−Meier survival curves.…”
Section: Discussionmentioning
confidence: 99%